Hubungan Pengetahuan, Dukungan Keluarga dan Tradisi Dengan Pemberian Makanan Pendamping Asi (MP-ASI) Pada Bayi Usia 0-6 Bulan - Nurlela Apriani; Rizki Amalia; Syarifah Ismed (Universitas Batanghari Jambi, 2022)
Early provision of complementary feeding (MP-ASI) is very dangerous, especially if it is served unhygienic. Infants who received MP-ASI before the age of six months were more likely to develop diarrhea, constipation, cold cough and fever when compared to infants who were exclusively breastfed. This study aims to determine the relationship between knowledge, family support and tradition with complementary feeding for infants 0-6 months in Kartamulia Village, Lubuk Batang District, Ogan Komering Ulu Regency in 2021. The design of this study is an analytical survey using a cross sectional research design. The population in this study were all mothers who had babies aged 0-6 months as many as 33 respondents and the number of samples as many as 33 respondents. The sampling technique used is Total Sampling. Data analysis used chi square statistical test with p value value (0.05). The results of this study from 33 respondents studied found that there was a relationship between knowledge (p value = 0.01), family support (p-value = 0.03), and family traditions (p-value = 0.03) with complementary feeding. (MP-ASI) in infants aged 0-6 months. The results of this study can be used as a reference to improve counseling and socialize the impact of giving MP-ASI too early on the community.